Analisis Perbandingan Baterai Lithium-Ion, Lithium-Polymer, Lead Acid dan Nickel-Metal Hydride pada Penggunaan Mobil Listrik - Review - Afif, Muhammad Thowil; Pratiwi, Ilham Ayu Putri (Jurusan Teknik Mesin, Fakultas Teknik, Universitas Brawijaya, 2015)
A battery is an important part of electric vehicle which is converting the chemical energy into electrical energy. There are two types of battery based on the occurrence i.e. primary and secondary batteries. In the market there are a lot of secondary battery types for electric vehicle i.e. Lithium-ion, Lithium Polymer, Lead acid, and Nickel Metalh Hydrarde batteries. Because of that, a study comparation of secondary battery types was needed. Meta-analysis method was used to analyze the comparison between secondary battery types. The results showed that each battery have different spesifications, advantages, and disadvantages. There are a lot of consideration to choose battery for electric vehicle including initial cost, life time, mass, volume, temperature sensitivity, acces to care and acces to product.